You wouldn't want to sail on the Titanic! : one voyage you'd rather not make - Stewart, David (David Evelyn), 1954-; Antram, David, 1958-; Salariya, David (New York : Franklin Watts, 2001)
Illustrations and simple text teach young readers about the maiden voyage and sinking of the Titanic.
Includes index.
Library Talk.
5.5.
5.5
3-6
Keywords: Titanic (Steamship) -- Juvenile literature; Titanic (Steamship); Titanic (Steamship); Shipwrecks -- North Atlantic Ocean -- Juvenile literature; Shipwrecks; Shipwrecks